FENOMENA BERITA HOAX GROUP WHATSHAPP UMMU DISCUSSION MENJELANG PILPRES 2019 - Bailussy, Wahyuni; Ariani Simabur, Lisda (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2019)
In order to avoid random communication interactions, and lead to interaction inconvenience. The library research method that collects data from books, articles and the internet. Data collection was conducted in Ternate City focused on Muhammadiyah University of North Maluku. Observing and analyzing communication activities that occurred among lecturers who were participants in the Ummu Discussion group, in response to news of presidential and vice presidential Hoax ahead of the 2019 presidential election. Based on researchers' observations there were several hoax news that were disseminated in the group Discussion and triggered controversial comments between groups grouped. communication that is built between group participants is very varied, some are pro with issues that are disseminated and there are also those who contradict the hoax issue. The group participants turned out to be hooked on hoax news that was spread so that there were skewed responses about the object of information received and the defense of hoax news objects.